2010 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--15763
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Third World Poverty In First Year Engineering Capstone Projects: Initial Findings

Abstract: He received his doctorate from the University of Illinois at Urbana-Champaign. His areas of research include simplifying the outcomes assessment process, first-year engineering instruction, and the pedagogical aspects of writing computer games. Dr. Estell is a Senior Member of IEEE, and a member of ACM,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…These components may help educators create strong learning scaffolds to help students manage the complexity of designing for people living in poverty. 23 I found engineering design educators 24,25 who used reflection to identify learning needs of their students developed these stronger scaffolds intrinsically. Furthermore, I wanted to offer guidance to engineering educators assessing student work that targeted marginalized communities around the world.…”
Section: Translating Theoretical Framework Of Wellbeing For Purposes Of Design Assessmentmentioning
confidence: 99%
“…These components may help educators create strong learning scaffolds to help students manage the complexity of designing for people living in poverty. 23 I found engineering design educators 24,25 who used reflection to identify learning needs of their students developed these stronger scaffolds intrinsically. Furthermore, I wanted to offer guidance to engineering educators assessing student work that targeted marginalized communities around the world.…”
Section: Translating Theoretical Framework Of Wellbeing For Purposes Of Design Assessmentmentioning
confidence: 99%
“…For many years, students in the first-year introduction to engineering course sequence at Ohio Northern University have used poverty alleviation in developing countries as a theme for their culminating design experience. [5,6] However, the results of course assessments indicated that students had difficulty in understanding how the real world can influence and thereby constrain design. The CSM was subsequently developed as a tool for exposing students to potential sources of design constraints and shared last year with the first-year and design communities.…”
Section: Introductionmentioning
confidence: 99%
“…The CSM was subsequently developed as a tool for exposing students to potential sources of design constraints and shared last year with the first-year and design communities. [7,8] In the fall of 2016 a study was conducted to evaluate how engineers at various experience levels -first-year, seniors, and practicing professionals -use this tool to perform constraint analysis. [9] For this research, a subset of 15 design attributes (shown as shaded attributes within Table I) was used, so as to not overwhelm the first-year students serving as the baseline for this study.…”
Section: Introductionmentioning
confidence: 99%